Endurance performance with acute ingestion of dietary nitrate supplementation in trained and untrained individuals - Mohd Saleh, Maisarah; Omar Dev, Roxana Dev; Linoby, Adam; Ab Razak, Rozella; Norhamazi, Iqbal; Syed Zubir, Syed Murshid; Tengku Kamaldeen, Tengku Fadhilah (Pitesti University Publishing House, 2023)
Nitric oxide (NO) has emerged as a critical regulator of vascular function and exercise performance. Dietary sources rich in nitrates, such as beetroot, have been investigated for their potential to enhance NO production, thereby improving cardiovascular health and exercise capacity. Previous research suggests that acute supplementation with nitrate-rich beetroot crystals (BRC) may enhance high-intensity intermittent exercise performance. However, there is limited understanding of how such supplementation affects both trained and untrained individuals and the mechanisms underlying its effects. The current study investigated the effect of acute supplementation of nitrate-rich beetroot crystal (BRC) on the improvement of high-intensity intermittent running performance in trained and untrained males. The current study investigated the acute supplementation of nitrate-rich beetroot crystal (BRC) on the improvement of high-intensity intermittent running performance in trained and untrained males. In a randomized, double-blind, and crossover study, thirty males (VÌ‡ O2 max 46.45± 4.8 ml-1·kg-1·min-1) consumed an acute dose of beetroot crystals (BRC; 25 g·dayˆ’1 containing ~8.1 mmol of NO3 ”), or 25 g·dayˆ’1 placebo (PLA: maltodextrin) 1.5 hour before commenced Yo-Yo Intermittent Recovery Test Level 1(YYIRLT1). BRC improved YYIRLT1 in the untrained group, not in the trained group (BRC: 1087m ± 205.4 vs. PLA: 981.8m ± 137.8; p0.05). These findings suggest that BRC may be a useful tool for enhancing exercise performance in untrained individuals and may have additional benefits for cardiovascular health.